Incidence of adverse events after loading phase of the brolucizumab therapy of neovascular AMD: Real-life evidence in the Czech Republic. Issue 2 (March 2023) - Stepanov, Alexandr; Studnicka, Jan; Veith, Miroslav; Nemec, Pavel; Vyslouzilova, Daniela; Koubek, Michal; Nemcansky, Jan
Aim: To evaluate the incidence of ocular adverse events after loading phase of the brolucizumab therapy in patients with neovascular age-related macular degeneration (nAMD) in real-life clinical practice – in treatment-naive patients and in patients after switching from another anti-VEGF agent. Another aim was to evaluate treatment outcomes in patients with adverse events. Methods: This is a multicentre, retrospective, observational study from 16 application centres in the Czech Republic. Patients diagnosed with nAMD were treated with brolucizumab in a fixed regimen of loading phase (3 injections administered at one-month intervals) and the mean follow-up period was 120 ± 10 days after the first injection. The incidence of adverse events and the development of best corrected visual acuity (BCVA) and central retinal thickness (CRT) in patients with complications were evaluated. A total of 1, 098 eyes were followed up, of which 783 were treatment-naive and 315 eyes were after switching from another anti-VEGF agent. Results: Adverse events were recorded in 42 eyes (3.83%), of which 30 eyes were treatment-naive (2.7%) and 12 eyes were post-switch (1.09%). The mean baseline BCVA ± SD was 56.7 ± 10.7 ETDRS chart letters in the group of patients with adverse events, 58.8 ± 10.1 letters in treatment-naive patients, and 51.4 ± 10.2 letters in patients after switch from another anti-VEGF agent. The mean baseline CRT ± SD was 432.2 ± 154.7 μm, being 435.8 ± 137.3 μm in treatment-naive patients and 424.5 ± 186.6 μm in patients after switch from another anti-VEGF agent. At the end of the follow-up, the mean BCVA ± SD was 53.4 ± 9.5 ETDRS charts letters in patients with adverse events, 55.6 ± 10 letters in treatment-naive patients, and 47.6 ± 10 letters in patients after switching from another anti-VEGF agent. The mean CRT ± SD at the end of the follow-up was 300.7 ± 115.7 μm in the total patient cohort, 285.2 ± 78.8 μm in treatment-naive patients and 334.5 ± 165.4 μm in patients after switching from another anti-VEGF agent. Conclusion: We observed the development of adverse events in the form of intraocular inflammation or vasculitis with subsequent decrease in BCVA in 3.83% of cases after loading phase of the brolucizumab therapy. The decrease in BCVA was reversible in most cases after initiation of anti-inflammatory steroid treatment. From a functional and morphological point of view, we did not demonstrate any statistically significant difference between the groups of treatment-naive patients and patients after switching from another anti-VEGF agent.